A biomarker signature to predict complete response to itacitinib and corticosteroids in acute graft‐versus‐host disease. (11th June 2022) - Pratta, Michael; Paczesny, Sophie; Socie, Gerard; Barkey, Natalie; Liu, Hao; Owens, Sherry; Arbushites, Michael C.; Schroeder, Mark A.; Howell, Michael D.
Summary: A broad proteomic analysis was conducted to identify and evaluate candidate biomarkers potentially predictive of response to treatment with an oral selective Janus kinase 1 (JAK1) inhibitor, itacitinib, in acute graft‐versus‐host disease (GVHD). Plasma samples from 25 participants (identification cohort; NCT02614612) were used to identify novel biomarkers that were tested in a validation cohort from a placebo‐controlled, randomised trial ( n = 210; NCT03139604). The identification cohort received corticosteroids plus 200 or 300 mg itacitinib once daily. The validation cohort received corticosteroids plus 200 mg itacitinib once daily or placebo. A broad proteomic analysis was conducted using a proximity extension assay. Baseline and longitudinal comparisons were performed with unpaired t ‐test and one‐way analysis of variance used to evaluate biomarker level changes. Seven candidate biomarkers were identified. Monocyte‐chemotactic protein (MCP)3, pro‐calcitonin/calcitonin (ProCALCA/CALCA), together with a previously identified prognostic acute GVHD biomarker, regenerating islet‐derived protein (REG)3A, stratified complete responders from non‐responders (participants with progressive disease) to itacitinib, but not placebo, potentially representing predictive biomarkers of itacitinib in acute GVHD. ProCALCA/CALCA, suppressor of tumorigenicity (ST)2, and tumour necrosis factor receptor (TNFR)1 were significantly reduced over time by itacitinib in responders, potentially representing response‐to‐treatment biomarkers. Novel biomarkers have the potential to identify patients with acute GVHD that may respond to itacitinib plus corticosteroid treatment (NCT02614612; NCT03139604).